The Scope of Philosophy of Science: Contemporary Islamic Education Perspectives - Muhamad Ihsannudin; Khusnul Khotimah; Agus Suprayogi (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2026)
This study examines the scope of Islamic philosophy of science—ontology (the essence of science as God's creation encompasses four realms of reality centered on monotheism), epistemology (the sources of revelation—the Qur'an/Sunnah supplemented by reason/the senses/bayani-burhani-'irfani methods, including Al-Ghazali's Nine-Stage System), and axiology (ethics of revelation for caliphate and eternal happiness)—in the context of contemporary Islamic education. Historically, the evolution began with the synthesis of Al-Kindi/Farabi/Sina (early classical), the critique-synthesis of Al-Ghazali/Khaldun (middle), to the ijtihad of Abduh, the Islamization of al-Attas, the perennialism of Nasr (contemporary), and the Islamist deconstruction of Ramadan in the digital age (modern). Using descriptive library research methods with content analysis of national/international journals, this comparative study identifies a paradigm shift: from normative texts to rational-critical-integrative ones, supporting blended learning, AI ethics, and a holistic curriculum that prevents secularization for the sake of intellectually and morally competitive insan kamil. The findings affirm the philosophy of science as a bridge between revelation and empirical reason, relevant to globalization/technology, with implications for the formation of an adaptive Islamic civilization based on tawhid.